Synergic effect of recycled cotton fabric and wood saw dust reinforced biodegradable polypropylene composites - Islam, MK; Sharif, A; Hussain, M; Hassan, I (Bangladesh Journal of Scientific and Industrial Research, 2019)
Hybrid polymer matrix composites of waste cotton fabric and wood saw dust reinforcements were studied with a view to recycling the wastes from garments and carpentry industries. Polymer composites with cotton fabric and wood-saw-dust reinforcements were fabricated using hot press machine. Their physical, thermal and mechanical behaviors were discussed in terms of moisture absorption, thermal stability, tensile strength, elastic modulus, flexural strength and flexural modulus. Compositional analyses of fibers, matrix and composites were carried out with FTIR spectroscopy. Experimental results revealed that tensile and flexural strength of the composites increased with cotton fabric reinforcement. On the other hand, with increasing wood saw dust strength decreased up to a certain limit and then increased again. Water absorption of the hybrid composites increased substantially with increasing natural filler contents. Maximum water absorption was observed in 20% fabric/wood-saw-dust reinforced polymer composite. Furthermore, TGA graphs suggest better thermal stability of the hybrid composites than that of pure polypropylene. Bangladesh J. Sci. Ind. Res.54(1), 21-30, 2019